A witch's life in Mongol. 2 - Tomato Sūpu (Comic book writer) (Yen Press, 2025)
"Sitara spent her youth in the service of a scholarly household, where she was treated like family--the best life a slave like her could hope for in 13th century Iran. Then the Mongol invasions ripped it all away. Her home was burnt. Her beloved mistress was killed before her eyes. And she was dragged into the strange and unknown steppes... But Sitara adapts fast. Adopting her mistresses name, "Fatima," she has used her education to become a vital asset in the Mongol court...where she bides her time for revenge. Has the hour come at last, now that Genghis Khan has died?"--Provided by publisher.